Estudo de parâmetros para a avaliação de cursos de ensino a distância (EAD) - Faller, Lisiane Pellini (2009)
In the new socio-economic world order, the education theme presents itself in a constant concern of governments in minimize the social differences. Thus, the distance education emerges as a new ideological proposal of social reorganizing, taking care of different populations with some difficulties related to the education access. To that end, appears the distance graduate course in Special Education of the Federal University of Santa Maria, a Pilot Project of that institution, as well as many others that are offered every year in various Higher Education Institutions (IES) in Brazil, public or private. Thus, the general objective of the dissertation, which had how study focus the Pilot Project of UFSM, is to propose parameters for the evaluation of the distance education courses aimed at Higher Education Institutions of public and/or private nature.The search was characterized by the descriptive nature whose the adopted method was the case study, applied in the Special Education course, distance modality, of UFSM. According to the characteristics of the research problem, it was chosen a quantitative- qualitative study, through 75 questionnaires applied to the students in three places of actuation, Bagé, Santana do Livramento and Uruguaiana, and through 13 interviews with teachers, tutors and coordinators. Through data analysis, it was possible to confirm that the Pilot Project in Distance Education of UFSM, through the Special Education Course, showed an absence of satisfaction related to the structures offered in the mentioned places, however most issues received high grades which indicate a general satisfaction of all involved with this sort of education offered by the Institution. The study allowed, through the application and examination of instruments, proposals of parameters to evaluate the distance education that being offered in Brazil, both in public as private institutions, in order to provide tools capable of to evaluate the way that is occurring the process of legitimacy of this mode of teaching and the level of distance education that Brazil is allowing to institutionalize.